Hind Swaraj: Gandhi's Vision of the Body, Society, and Philosophy in the Quest for Self-Rule (Patan Prospective Journal, 2024)
This paper explores Mahatma Gandhi's Hind Swaraj as a profound philosophical treatise that extends beyond its political narrative to address fundamental questions about the nature of the body, society, and the ideal human condition. It delves into Gandhi's conceptualization of the body, arguing that his holistic understanding forms the foundation for his critique of modern civilization and his advocacy for Swaraj (self-rule). Gandhi's views on the body emphasize the importance of moral and spiritual health alongside physical well-being, challenging the materialistic and reductionist approach of Western medicine. By defining society as an organic whole, Gandhi critiques the individualism of modern civilization and promotes a vision of a decentralized, self-sufficient, and ethically grounded community life. This paper also examines Gandhi's core philosophical principles of ahimsa (nonviolence) and satyagraha (truth-force), demonstrating how these concepts are interwoven with his understanding of the body and society. Through a qualitative analysis of Hind Swaraj and contextual insights from secondary sources, the paper aims to uncover the intricate connections between Gandhi's critique of modernity and his vision for a self-ruled India. Ultimately, it argues that Gandhi's philosophy offers a comprehensive framework for understanding the interplay between individual well-being and societal health, presenting a timeless and holistic approach to personal and social transformation.